Examining PM2.5 concentrations in counties with and without state-run correctional facilities in Texas - Block, Kristina (Punishment & society, 2024)
A high percentage of people who are incarcerated suffer from health problems that affect them both in prison and after they are released. Environmental hazards and pollutants can exacerbate these problems as well as contribute to the development of new health conditions. One specific type of pollutant that is associated with a wide array of health problems including decreased lung function, cancer, and asthma is particulate matter smaller than 2.5 µm (PM2.5). While prior research indicates that PM2.5 is not equally distributed throughout space, it remains unknown if levels of PM2.5 differ in areas with and without correctional facilities. The current study aims to address this gap by examining if counties with state-run correctional facilities have higher concentrations of PM2.5 relative to counties without state-run correctional facilities in Texas. Results of OLS regression models indicate that counties with one or more state-run correctional facilities have higher concentrations of PM2.5 relative to counties without these facilities. These findings highlight the importance of improving prison healthcare and addressing issues of environmental injustice in correctional facilities.